Catalytic Synthesis of Pyrazolo[3, 4-d]pyrimidin-6-ol and Pyrazolo[3, 4-d]pyrimidine-6-thiol Derivatives Using Nanoparticles of NaX Zeolite as Green Catalyst. (4th April 2013) - Gharib, Ali; Jahangir, Manouchehr; Roshani, Mina; Moghadasi, Sara; Safee, Reza
Abstract : An efficient and environmental benign method is reported for the synthesis of some pyrazolopyrimidine derivatives using 3-methyl-1-phenyl-5-pyrazolone with carbonyl compounds in the presence of nanozeolite Nax catalysts, solvent-free and at reflux conditions. It is noteworthy to mention that this method of the synthesis requires less time, less temperature, and better yield.